(untitled) (Cardiovascular Journal, 2021)
Background: The novel corona virus (COVID 19) pandemic is a major global health threat of the twenty-first century. Clinical presentation, rapid identification of causes and isolation are vital for containments of rapidly spreading disease. The objective of the study was to report early findings on demographic profile, clinical presentation of the confirmed COVID 19 patients with their clinical outcome. Methods: This observational study was conducted in Microbiology Department of National Institute of Cardiovascular Diseases (NICVD) for the period of October 01, 2020 to November 30, 2020. Total 300 positive COVID 19 patients were included and interviewed. Informed written consent was ensured before participation. After collection, Data were analyzed to show the characteristics of COVID 19 cases and their clinical outcome after treatment. Results: Among the 300 cases 228 (76%) patients were male and 72 (24%) patients were female. Average age of the patients was 39 years. The most commonly observed symptoms were fever (70%), followed by cough (55%), breathlessness (42%), dysgeusia (38%), anosmia (25%). Respiratory symptom was the dominant feature of clinical presentation. The most prevalent affected age groups were 114 (38%) patients in 41-50 years age, 102 (34%) patients in 31- 40 years age. Among the total cases 255 (85%) patients were Urban residents and 234 (78%) had contact history. Among 300 patients 102 (34%) patients had co-morbidities and presence of co-morbidities (p<0.01) were significantly associated with mortality. The death rate was 2%. Conclusion: Typical presentations of COVID-19 were fever, cough, breathlessness, dysgeusia and anosmia. Requirement of ICU was 6% and overall mortality was 2% which was associated with comorbidities. Cardiovasc j 2021; 14(1): 50-54